Penerapan Model Pembelajaran Think Talk Write terhadap Hasil Belajar IPS Kelas V - Anggraini, Sinta; Sofiarini, Andriana; Frima, Aren (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completeness of student learning outcomes after the implementation of the Think Talk Write Learning Model in the subject of social studies of grade V students of SD Negeri 1 Ngestiboga II. This type of research is quantitative research and the research method used is a quasi-experiment using a pre-test and post-test research design. Using essay questions totaling 15 questions, the sample of the study was class V consisting of 28 students. Data analysis techniques with the following steps: normality test, Z test. The average pre-test score is 4.470 and the average post-test score is 79.70. Based on the results of the z-test analysis, the Zcount value (71.8) and Ztable 1.64 if compared, then Zcount> Ztable. The conclusion is that the social studies learning outcomes of grade V students of SD Negeri 1 Ngestiboga II after the implementation of the Think Talk Write Learning Model are significantly complete. Keywords: Learning Outcomes, Think Talk Write, Social Studies Learning